The Influence Of Work Discipline, Organizational Commitment And Motivation For Employee Performance Communication And Information Service Binjai City - Syafwan Nabawi; Fitra Arlina Nasution; Rifky Budi Setiawan (International Journal of Management, Economic and Accounting, 2025)
The research analysis aims to find out whether Work Discipline, Organizational Commitment, and Motivation affect the performance of Binjai City Communication and Information Service employees. The data analysis technique used is an associative research method with the help of the SPSS version 25 program. This research uses multiple linear regression analysis. The sample in this study was 45 respondents. Primary data collection uses a questionnaire. The results of the research show that work discipline has a partially positive and significant effect on the performance of employees of the Binjai City Communication and Information Service. Organizational commitment has a partially positive and significant effect on the performance of employees of the Binjai City Communication and Information Service. Motivation hasno a partially effect on the performance of employees of the Binjai City Communication and Information Service. Work discipline, organizational commitment and motivation simultaneously have a positive and significant effect on the performance of employees of the Binjai City Communication and Information Service.